EFEKTIVITAS PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN TERNAK BABI PADA GAPOKTAN OLADIKE DI DESA KWAELAGA LAMAWATO, KECAMATAN ADONARA TIMUR, KABUPATEN FLORES TIMUR (Effectiveness of the rural agribusiness development program for pig farming in....) - Hendrikus T. Sanga; Ulrikus Romsen Lole; Yohanes G. Sogen; Maria Krova (JURNAL NUKLEUS PETERNAKAN, 2022)
The PUAP program is a program developed by the Ministry of Agriculture to address problems in agribusiness related to capital, marketing, human resources, business management, and group management that have an influence on farmer productivity. However, the problem that wants to be studied is how the level of effectiveness of the PUAP program on pig farms in Gapoktan Oladike, Kwaelaga Lamawato Village, East Adonara District, East Flores Regency. The aim of the study was to analyze the effectiveness of the PUAP program on pig farming in the Oladike Farmers' Association. The research was conducted in the village of Kwaelaga Lamawato which includes a group of farmers in the Oladike Gapoktan. Respondents were taken from group members, group administrators, PPL, village heads, related offices, and other stakeholders. Data analysis uses effectiveness analysis to analyze the effectiveness of the PUAP program. The conclusion of the study is that based on Likert's assessment and the percentage of the effectiveness of the program's inputs, processes, and outputs, it turns out to be in the effective category, so that in general the Rural Agribusiness Development Program (PUAP) in the pig farming business has carried out the PUAP program well by Gapoktan Oladike. It is recommended that with better business management, the PUAP program will have a positive impact so that it is expected to maintain its sustainability, both the PUAP program and similar programs.